Focus groups a practical guide for applied research - Krueger, Richard A. (Sage Publications, 1994)
The highly acclaimed first edition of Richard Krueger's Focus Groups has become the standard introduction to this widely used technique. Retaining its focus on applied research and its step-by-step approach to planning and conducting a successful focus group, this new edition has been expanded to offer broader coverage on analyzing focus group results and exploring various collaborative approaches. It also includes additional material on questioning strategies, moderator roles, selecting participants, and accounting for cultural diversity within a focus group.